Sosialisasi dan Implementasi Sistem Manajemen Tata Graha 5S di PT. PLN Nusantara Power - Moch. Syaiful Anwar; Bambang Triono; Mochamad Shaleh (ALKHIDMAH: Jurnal Pengabdian dan Kemitraan Masyarakat, 2024)
The increasing demands of industrial environments require companies to develop efficient, orderly, and safe workplace systems. One approach that supports this need is the 5S workplace management system, consisting of Seiri, Seiton, Seiso, Seiketsu, and Shitsuke. This community service activity aims to improve workers’ understanding and application of the 5S concept at PT. PLN Nusantara Power through socialization and direct implementation. The program was conducted on 15–16 April 2024 involving 20 participants. The implementation method consisted of four stages: preparation, socialization, practical implementation, and evaluation. Socialization was delivered interactively to introduce the basic concepts and benefits of 5S in industrial settings, while the implementation stage involved direct practice in workplace organization, sorting, and cleaning activities. Evaluation was carried out through pre-test and post-test assessments, observation, and reflective discussion. The results show a significant increase in participants’ understanding of 5S, from 30% at the initial stage to 75% after the program. This improvement indicates that combining theoretical explanation with hands-on practice is effective in enhancing comprehension and awareness of workplace organization systems.